10+2(2x-3)=17-(3x-8)

Simple and best practice solution for 10+2(2x-3)=17-(3x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+2(2x-3)=17-(3x-8) equation:


Simplifying
10 + 2(2x + -3) = 17 + -1(3x + -8)

Reorder the terms:
10 + 2(-3 + 2x) = 17 + -1(3x + -8)
10 + (-3 * 2 + 2x * 2) = 17 + -1(3x + -8)
10 + (-6 + 4x) = 17 + -1(3x + -8)

Combine like terms: 10 + -6 = 4
4 + 4x = 17 + -1(3x + -8)

Reorder the terms:
4 + 4x = 17 + -1(-8 + 3x)
4 + 4x = 17 + (-8 * -1 + 3x * -1)
4 + 4x = 17 + (8 + -3x)

Combine like terms: 17 + 8 = 25
4 + 4x = 25 + -3x

Solving
4 + 4x = 25 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
4 + 4x + 3x = 25 + -3x + 3x

Combine like terms: 4x + 3x = 7x
4 + 7x = 25 + -3x + 3x

Combine like terms: -3x + 3x = 0
4 + 7x = 25 + 0
4 + 7x = 25

Add '-4' to each side of the equation.
4 + -4 + 7x = 25 + -4

Combine like terms: 4 + -4 = 0
0 + 7x = 25 + -4
7x = 25 + -4

Combine like terms: 25 + -4 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 3y+78= | | (2x+9)(x+8)=0 | | 8d-22=52 | | 2s+4.6=3s-1.2 | | 5x-32=43 | | 3(m+10)= | | 7x^2=73 | | -5600+200x=0 | | -7(z+4)+3z= | | g-0+4g+6=12 | | 2x*1=x+4 | | -x^2+18x-65=0 | | x/6+7=18 | | r-4/5=-21/4 | | x^3-14x^2y+24xy^2= | | -7(2+4)+32= | | 3(n+2)+15n=114 | | 7x=7(x-2) | | 6x-8=70 | | 6x=2(5x+12) | | 0.75x=-15 | | 9a-3(a-6)=66 | | -25+8t+6m-4t-4m+29= | | 15*36= | | -6(6x+6)= | | (x+6)3=33 | | 2x/4+2=6 | | 15.36= | | 8*3x+1=128 | | -5y=20 -10x | | 4d-22=48 | | z-.66=.125 |

Equations solver categories